The Structural And Functional Features Of Polysemy In The Process Of Translation In The Uzbek And English Languages - Bolibekova, Mavjuda Mardievna; Elmuratova Nafisa Хajibaevna; Mirsagatova, Pokiza Avazbek qizi; Alimjanova, Shohsanam Azamat qizi (The journal of contemporary issues in business and government, 2021)
In fact, the emotive potential of the language is high and polysemy is a great advantage to a language, so the article illustrates the structural and functional features of polysemy in translation, differences and similarities in the usage; classification of polysemy in the Uzbek and English languages. The paper deals with also the problems of translation of polysemy in both languages by using comparative and contrastive analysis of observation.